Evaluation of potential bacterial protease inhibitor properties of selected hydroxyquinoline derivatives: an in silico docking and molecular dynamics simulation approach - Riaz, Faiza; Hossain, Md. Sanower; Roney, Miah; Ali, Yousaf; Qureshi, Saira; Muhammad, Riaz; Moshawih, Said; Abd Hamid, Shafida; Seidel, Veronique; Rashid, Haroon ur; Ming, Long Chiau (Taylor & Francis, 2022)
Antimicrobial drug resistance (AMR) is a severe global threat to public health. The increasing emergence of drug-resistant bacteria requires the discovery of novel antibacterial agents. Quinoline derivatives have previously been reported to exhibit antimalarial, antiviral, antitumor, antiulcer, antioxidant and, most interestingly, antibacterial properties. In this study, we evaluated the binding affinity of three newly designed hydroxyquinolines derived from sulfanilamide (1), 4-amino benzoic acid (2) and sulfanilic acid (3) towards five bacterial protein targets (PDB ID: 1JIJ, 3VOB, 1ZI0, 6F86, 4CJN). The three derivatives were designed considering the amino acid residues identified at the active site of each protein involved in the binding of each co-crystallized ligand and drug-likeness properties. The ligands displayed binding energy values with the target proteins ranging from 2.17 to 8.45 kcal/mol. Compounds (1) and (3) showed the best binding scores towards 1ZI0/3VOB and 1JIJ/4CJN, respectively, which may serve as new antibiotic scaffolds. Our in silico results suggest that sulfanilamide (1) or sulfanilic acid (3) hydroxyquinoline derivatives have the potential to be developed as bacterial inhibitors, particularly MRSA inhibitors. But before that, it must go through the proper preclinical and clinical trials for further scientific validation. Further experimental studies are warranted to explore the antibacterial potential of these compounds through preclinical and clinical studies.